Pembuatan Stik Daun Kelor (Moringa oleifera) sebagai Upaya Peningkatan Gizi Jajanan Lokal - Irman Idrus; Syaiful Katadi; Nurfitriyana Rahmat; Muh. Ramadhan Salam; Rahayu Aprianti; Lilis Suriyani; Ummi Kalsum; Wiwin Trisilia; Afifah Fausiyah; Sri Yulia Ningsih; Elsa ti Damayan (JURNAL LENTERA ILMIAH PENGABDIAN MASYARAKAT, 2024)
Moringa oleifera leaves are known for their high nutritional content, yet their utilization remains limited. This study aimed to develop Moringa leaf-based sticks and evaluate their acceptance. An experimental method was employed, creating three stick formulations: control, 10% Moringa leaf powder (A), and 20% Moringa leaf powder (B). Proximate analysis, organoleptic tests, and community acceptance surveys were conducted. Results showed significant protein, vitamin A, and iron increases in Moringa-fortified sticks. Formulation A had the best acceptance with an average score of 4.2 out of 5 for all organoleptic parameters. Despite higher nutritional value, Formulation B was less preferred due to stronger color intensity and aroma. The survey revealed that 85% of respondents were interested in consuming Moringa sticks regularly. Education and demonstration of stick-making to the community increased interest, with 78% of respondents willing to try making them at home. In conclusion, Moringa leaf sticks have the potential to become a healthy snack alternative that can improve community nutritional intake. Further research on nutrient stability during storage and formulation optimization is needed for better acceptance..